PERBEDAAN SOSIALISASI NILAI PERTANIAN OLEH AGEN SOSIALISASI PRIMER KEPADA PEMUDA DAN PEMUDI DI PEDESAAN (KASUS DESA CIASMARA, PAMIJAHAN, BOGOR) - Nugraha, Yogaprasta Adi; Muslim, Muslim (Universitas Sebelas Maret, 2021)
The phenomenon related to the low participation of young people to work in the agricultural sector, it is necessary to be studied more new perspectives. Moreover, the perspective of how agriculture itself is constructed by their social system, in this case, how parents and peers construct the notion of agriculture. The objectives of this study are 1) to identify the differences between the attitudes of male and female rural youth towards work in the agricultural sector, 2) to analyze differences in the patterns of socialization of parents and peers to male and female rural-youth about work in the agricultural sector, and 3) analyze the differences between the relationship patterns of socialization of parents and peers with the attitude of male and female rural youth towards agricultural work. This research was conducted in Ciasmara Village, Pamijahan Sub-district, Bogor District from July 2019 to February 2020 using quantitative research methods with a descriptive-comparative approach. A total of 69 young women and 60 young people were selected as research samples. This study found that there were differences in attitudes between male and female rural youth related to work in the rice agriculture sector. Parents were the actors who most highly socialize the value of agriculture to young men and women in the form of involving the activities of growing rice, cultivating land, and harvesting. Meanwhile, both parents and peers have positively correlated with the attitudes of young men and women about work in the agricultural sector.